1994
DOI: 10.1016/0266-7681(94)90139-2
|View full text |Cite
|
Sign up to set email alerts
|

Extensor Tendon Sheath Stenosis Resulting in Triggering of the Little Finger

Abstract: An isolated constriction of the tendon sheath of extensor digiti minimi caused triggering of the little finger. Incision of the tendon sheath resulted in recovery of frictionless gliding of the tendon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 4 publications
3
8
0
Order By: Relevance
“…Seradge et al reported that the EDM tendon slips were served with an accessory pulley 2 cm distal to the distal end of the extensor retinaculum (Seradge et al, 1999). Others have made similar observations (Yamaguchi et al, 1984;O'Rourke et al, 1994;Rokkaku et al, 2004). O'Rourke reported that the triggering of the little finger seen in tenosynovitis of the 5th dorsal compartment was localized to a pulley on the dorsum of the wrist 4 cm proximal to the head of the fifth metacarpal (O'Rourke et al, 1994).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Seradge et al reported that the EDM tendon slips were served with an accessory pulley 2 cm distal to the distal end of the extensor retinaculum (Seradge et al, 1999). Others have made similar observations (Yamaguchi et al, 1984;O'Rourke et al, 1994;Rokkaku et al, 2004). O'Rourke reported that the triggering of the little finger seen in tenosynovitis of the 5th dorsal compartment was localized to a pulley on the dorsum of the wrist 4 cm proximal to the head of the fifth metacarpal (O'Rourke et al, 1994).…”
Section: Discussionsupporting
confidence: 64%
“…Others have made similar observations (Yamaguchi et al, 1984;O'Rourke et al, 1994;Rokkaku et al, 2004). O'Rourke reported that the triggering of the little finger seen in tenosynovitis of the 5th dorsal compartment was localized to a pulley on the dorsum of the wrist 4 cm proximal to the head of the fifth metacarpal (O'Rourke et al, 1994). A synovial septum was noted to be present around the pulley.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…O'Rourke et al 11 reported a case of triggering of the fifth finger as a result of constriction of the extensor tendon sheath. These authors localized this subject's triggering within the tendon sheath of the EDM distal to the tendon's division into its terminal slips (distal to the extensor retinaculum).…”
Section: Discussionmentioning
confidence: 98%
“…On extensive search, we found very few reports of extensor tendon triggering in the literature [4][5][6][7]. Extensor triggering is usually caused by disruption or laxity of the sagittal bands that stabilize the extensor digitorum communis tendon over the metacarpal head [3,8].…”
Section: Introductionmentioning
confidence: 99%